2022
DOI: 10.3390/en15030883
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Waterfront Office Redevelopment Plan on Optimal Building Arrangements with Rooftop Photovoltaics: A Case Study for Shinagawa, Tokyo

Abstract: Designing waterfront redevelopment generally focuses on attractiveness, leisure, and beauty, resulting in various types of building and block shapes with limited considerations on environmental aspects. However, increasing climate change impacts necessitate these buildings to be sustainable, resilient, and zero CO2 emissions. By producing five scenarios (plus existing buildings) with constant floor areas, we investigated how buildings and district forms with building integrated photovoltaics (BIPV) affect ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Under the energy consumption topic (Garcia et al, 2021), compared the greenhouse emissions associated with conventional (346,569 kg CO 2 eq/year) and solar absorption (144,452 CO 2 eq/year) cooling systems installed at a university building, suggesting that new technology should be used in universities to decrease energy consumption patterns. In this regard, digitalization, Information and Communication Technologies (ICT), and artificial intelligence (AI) can contribute to more intelligent use of energy (Parks and Wallsten, 2020;Choi et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Under the energy consumption topic (Garcia et al, 2021), compared the greenhouse emissions associated with conventional (346,569 kg CO 2 eq/year) and solar absorption (144,452 CO 2 eq/year) cooling systems installed at a university building, suggesting that new technology should be used in universities to decrease energy consumption patterns. In this regard, digitalization, Information and Communication Technologies (ICT), and artificial intelligence (AI) can contribute to more intelligent use of energy (Parks and Wallsten, 2020;Choi et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is estimated that the windows and facades possess an energy generation potential of 2.1 GWh annually, closer to the annual power output of rooftop solar panels, highlighting the necessity to increase on-site PV generation further using facades. Younghun [129] indicated that in 2018, the photovoltaic roof had achieved economic benefits, and by 2030, it will be significantly improved, with a return on investment period of six years. However, due to the spatial constraints of roofs in large buildings, rooftop PV contributes less (2-9%) to total building demand or CO 2 reduction.…”
Section: Japan [129]mentioning
confidence: 99%